Public perception of intelligent building in Malaysia case study of Klang Valley / Muhammad Khairi Anuar - Anuar, Muhammad Khairi (Faculty of Architecture, Planning and Surveying, 2015)
Technological changes and developments nowadays have shown that the buildings fully equipped with various facilities can be categorized as intelligent building. Due to technology changes and develops, the intelligent buildings building also have evolved over time to time. The intelligent buildings in Malaysia have been built over the years since the government introduces the Multimedia Super Corridor in 1996. The government’s 2020 version motivate for more intelligent building with innovative technology will develop for major base economic activities and improve the efficiency business of the multinational and local companies. This research analysed the public perception towards intelligent buildings in Malaysia by investigate the knowledge, understanding, experiences and opinion on the intelligent building among the public in Klang Valley. To be able to gather the necessary data, the researcher are need to use a several method to spread the information for more detail about the intelligent building systems. The survey methods were questionnaire survey, non-structured interview and analysis contents. The research will cover the following: the research design and method, the respondents or subjects to be studied which will include the sampling method, the data collection, and the data analysis.